The Effect of Islamic Microfinance on Empowering Rural Communities Through Environmentally Sustainable Business Practices - Ismi Hamdani; Sukirman Sukirman; Aytan Azizli (International Forum of Researchers and Lecturers, 2024)
This study explores the effect of Islamic microfinance on empowering rural communities through environmentally sustainable business practices. Rural areas often face significant financial exclusion, with limited access to ethical financial services, particularly for eco-friendly enterprises. Islamic microfinance, grounded in Sharia principles such as risk-sharing, ethical investment, and the prohibition of interest (riba), offers an alternative financing model that can potentially foster both economic and environmental sustainability. The objective of this research is to analyze the impact of Islamic microfinance on rural communities, focusing on income growth, the adoption of environmentally sustainable business practices, and social empowerment. Using a mixed-methods approach, the study combines field surveys and interviews with beneficiaries of Islamic microfinance institutions (IMFIs) in rural areas. Data collection tools included questionnaires, focus group discussions, and institutional reports. Key findings reveal that participants in Islamic microfinance programs experienced significant income growth, an increase in environmentally friendly entrepreneurship (e.g., organic farming and recycling businesses), and enhanced community participation and self-reliance. The discussion highlights how Sharia principles encourage ethical investment and sustainable practices, contributing to a triple-bottom-line impact—economic, social, and environmental. However, challenges such as limited awareness, lack of green finance literacy, and regulatory constraints were identified. A comparison between Islamic and conventional microfinance outcomes showed that Islamic microfinance offers a distinct advantage by integrating moral, social, and ecological responsibilities. The study concludes that Islamic microfinance can serve as a transformative tool for rural development, offering solutions to both economic and environmental challenges. The research underscores the need for supportive policy frameworks and further investigation into the long-term impacts of green Islamic finance.